IMPLEMENTATION OF POSITIVE CULTURE TO IMPROVE TEACHER PERFORMANCE AND MOTIVATION AT SDK GOUPARU - Meo, Raymundus N Lado (Jurnal Analisis Pendidikan Sosial, 2024)
This study aims to explore the implementation of a positive culture in enhancing the motivation and performance of teachers at SDK Gouparu. The research employs a school action research methodology, utilizing a combination of qualitative and quantitative approaches to gather comprehensive data. Data collection methods include interviews, questionnaires, and observations conducted before and after each cycle of the intervention. The findings indicate that the application of a positive culture significantly improves teachers' understanding, motivation, and performance. Initially, many teachers expressed confusion regarding the concept of a positive culture and faced challenges in its implementation due to a lack of training and support. However, through structured interventions, including workshops and collaborative activities, teachers reported increased clarity and commitment to fostering a positive learning environment. Results show a marked increase in teachers' motivation scores from 2.8 to 4.0 and performance ratings from 3.0 to 3.5, alongside a rise in student engagement from 50% to 70%. These outcomes suggest that a supportive and positive school culture not only enhances teacher effectiveness but also contributes to a more engaging learning experience for students. The study concludes that the implementation of a positive culture is essential for improving educational outcomes and recommends further research to explore long-term impacts and strategies for sustaining such initiatives in various educational contexts